GROUP WORK AND INDIVIDUAL STUDY IN LEARNING LANGUAGE. (Ustozlar uchun, 2026)
This article explores the effectiveness of group work and individual study in the process of language learning. The purpose of the study is to analyze and compare these two widely used learning approaches in order to identify their strengths and weaknesses. Group work is examined as a collaborative method that encourages communication, interaction, and the development of speaking and listening skills. It also highlights how working in groups can increase motivation and create a supportive learning environment.On the other hand, individual study is presented as a more independent approach that allows learners to focus on their personal goals, learn at their own pace, and improve areas such as grammar, reading, and writing. The article discusses how self-study helps develop discipline and responsibility, although it may limit opportunities for real-life communication practice.Furthermore, the article emphasizes that both methods have certain limitations when used separately. While group work may lead to distractions or unequal participation, individual study can sometimes result in a lack of motivation and feedback. Therefore, the study suggests that combining both approaches can lead to more effective language learning outcomes.In conclusion, the article argues that a balanced use of group work and individual study provides the most beneficial results for learners, as it allows them to develop both communicative competence and independent learning skills.